2+2(2v-1)=-2(7v-6)+2v

Simple and best practice solution for 2+2(2v-1)=-2(7v-6)+2v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+2(2v-1)=-2(7v-6)+2v equation:


Simplifying
2 + 2(2v + -1) = -2(7v + -6) + 2v

Reorder the terms:
2 + 2(-1 + 2v) = -2(7v + -6) + 2v
2 + (-1 * 2 + 2v * 2) = -2(7v + -6) + 2v
2 + (-2 + 4v) = -2(7v + -6) + 2v

Combine like terms: 2 + -2 = 0
0 + 4v = -2(7v + -6) + 2v
4v = -2(7v + -6) + 2v

Reorder the terms:
4v = -2(-6 + 7v) + 2v
4v = (-6 * -2 + 7v * -2) + 2v
4v = (12 + -14v) + 2v

Combine like terms: -14v + 2v = -12v
4v = 12 + -12v

Solving
4v = 12 + -12v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '12v' to each side of the equation.
4v + 12v = 12 + -12v + 12v

Combine like terms: 4v + 12v = 16v
16v = 12 + -12v + 12v

Combine like terms: -12v + 12v = 0
16v = 12 + 0
16v = 12

Divide each side by '16'.
v = 0.75

Simplifying
v = 0.75

See similar equations:

| 3x-29=6x-5 | | 1(t-6)+7t=4(2t+4)-13 | | 15x^4-30x^2+10=0 | | 30k+60=20k+80 | | 17x+18=12x-7 | | b-b+2b= | | 24(x-1)=-8(3-x)+16 | | -3x+3=4x+10 | | y=xsin^2*(2x) | | (x^3+y^4)dx-8xy^3*dy=0 | | -3(x+4)+4x=-24 | | 2(x+3)+7=8x-8 | | y=5/4x-7 | | 2s(t+-7)+-6t(s+3)= | | (4x+8)(8x-4)=0 | | 3x+9=8x+3 | | 5g-2+4g+20=180 | | (7x-4)=(x+32) | | y=-7x+b | | -3(x+4)+4x=-2 | | x/3+7=2 | | 4x+14=6/5+7 | | 74-22=13Y | | 7.92y=2.2x | | .10(x)+.25(y)=12.55 | | 39.95-0.49x=75 | | 8(j-3)=4j+9j+-14 | | 125+55x=400 | | X^2+y^2+2x+4y=20 | | 3y=8x | | -3(2x-4)+8x=20 | | 15y=5x |

Equations solver categories